ANALISIS KINERJA KEUANGAN PRIMER KOPERASI KEPOLISIAN DAERAH KALIMANTAN BARAT - Miftahul Muslim; Maria Ulfah; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract: This thesis is entitled "Analysis of Primary Financial Performance of Regional Police Cooperatives (POLDA) of West Kalimantan." The problem in this study is "What is the Primary Financial Performance of West Kalimantan Regional Police Cooperation (POLDA)?". The method used is descriptive method. The results of this study indicate that the level of liquidity is 930.73%, 1.056.09%, and 748.1%, given a very not ideal criteria with fluctuating developments but tends to decrease, the solvency ratio is 1,888.76%, 317.92%, 487.54%, given criteria not very ideal with fluctuating developments but tended to increase, profitability ratios were 50.74%, 38.71%, and 38.84%, given very good criteria with fluctuating developments but tending to decline, and ratios activity was 101.96%, 115.41%, and 101.44%, given very effective criteria with fluctuating development. In the fourth component of the ratio there is no change in the level of health of the financial condition, but changes occur in the value of the ratio. In 2015-2017, the increase in current ratio was due to a rise in current assets of 121.33% and current liabilities of 95.1%, a decrease in solvency due to an increase in total assets of 61.29% and total liabilities of 858.2%. 68% and an increase in gross income of 39.84%, and an increase in the receivable turnover ratio due to an increase in the number of sales of 88.17% and the total receivables averaging 66.25%. Keywords: Financial Performance Analysis, Cooperatives